Ответ:
4. 3. 12
--------------. - ----------------. + ---------------. =
(m+2)(m-2). (m+2)(m-2). (m+2)(m-2)
= 4m-8-3m-6+12. m-2. 1
---------------------- =. -----------------. =. -------
(m+2)(m-2) (m+2)(m-2). (m+2)
1/m+2
Объяснение:
4/m+2 - 3/m-2 + 12/m²-4
4/m+2 - 3/m-2 + 12/(m+2)*(m-2)
4*(m-2)-3*(m+2)+12 / (m+2)*(m-2)
4m-8-3m-6+12 / (m+2)(m-2)
m-2 / (m-2)(m+2)
1 / m+2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
4. 3. 12
--------------. - ----------------. + ---------------. =
(m+2)(m-2). (m+2)(m-2). (m+2)(m-2)
= 4m-8-3m-6+12. m-2. 1
---------------------- =. -----------------. =. -------
(m+2)(m-2) (m+2)(m-2). (m+2)
Ответ:
1/m+2
Объяснение:
4/m+2 - 3/m-2 + 12/m²-4
4/m+2 - 3/m-2 + 12/(m+2)*(m-2)
4*(m-2)-3*(m+2)+12 / (m+2)*(m-2)
4m-8-3m-6+12 / (m+2)(m-2)
m-2 / (m-2)(m+2)
1 / m+2